1970
DOI: 10.1111/j.1423-0410.1970.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods Used in the Preparation of Leucocyte‐Free Whole Blood and Erythrocyte Concentrates

Abstract: Abstract. The authors studied the degree of qualitative and quantitative deleucocytation of whole blood that can be obtained by washing and filtering. Based on the studies of 20 samples of blood it was established that successful deleucocytation can be expected only it combined procedures of washing and filtering are employed. The purpose of our present investigations was to determine to what extent can whole blood be deleucocyted by using current methods of blood preservation, or by combining these methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Still, leukoreduction obtained in our study was consistent with the values from previous studies on manual washing by other investigators. [ 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Still, leukoreduction obtained in our study was consistent with the values from previous studies on manual washing by other investigators. [ 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…STOCKER et al [20], discussing their finding of IgM lymphocytotoxic antibodies in 3 patients who had rejected renal allografts while on immunosuppression, suggested that synthesis of IgM antibodies might not be suppressed by current regimes. Careful separation of virtually all white cells [15] and additional measures such as the organisation of autologous transfusion programmes [l] may be necessary to prevent the production of leucocyte antibodies.…”
Section: Discussionmentioning
confidence: 99%